Negative affective reaction to partner's dominant behavior influences satisfaction with romantic relationship. (December 2017) - Sadikaj, Gentiana; Moskowitz, D. S.; Zuroff, David C.
Dominant behavior has been related to lower quality romantic relationships. The present study examined two processes through which dominant behavior affects the quality of romantic relationships: (1) the extent to which the partner's dominance increases the person's negative affect by thwarting the person's sense of autonomy and (2) the degree to which the person's negative affect in reaction to the partner's dominant behavior affects relationship satisfaction. Using an event-contingent recording (ECR) methodology, 92 cohabiting couples reported their dominant behavior, negative affect, and autonomy in interactions with each other during 20 days. Relationship satisfaction was measured at the end of the ECR period. The results indicated that when a partner engages in dominant behavior, the person experiences greater negative affect in part due to a sense of thwarted autonomy and that greater negative affective reaction in association with the partner's dominant behavior is related to lower relationship satisfaction in the person.